2010
DOI: 10.1143/apex.3.073003
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline CaMoO3and SrMoO3Films Grown by Pulsed Laser Deposition in a Reductive Atmosphere

Abstract: Single-crystalline thin films of CaMoO3 and SrMoO3 with a Mo4+ state perovskite structure have been epitaxially grown by pulsed-laser deposition from Mo6+ state ceramic targets. Phase-pure films were obtained on nearly lattice-matched perovskite substrates using argon gas flow during the deposition. Transport properties of the films are consistent with those of paramagnetic and metallic phases, whereas the residual resistivities are far lower than those reported previously for films and bulk polycrystals. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 14 publications
4
37
0
Order By: Relevance
“…The resistivity of the film is about two order of magnitude lower than that of the polycrystalline sample, indicating the grain-boundary scattering is a dominant source of enhanced resistivity in the previous data for polycrystalline samples. The present residual resistivity value for the epitaxial film is comparable to that of SrMoO 3 films as previously reported [9]. A tiny upturn of resistivity was observed below 9 K; at 2 K a negative magnetoresistance is discerned such as 1.2% at 9 T. This behavior might be related to a weak localization effect arising from an impurity scattering.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The resistivity of the film is about two order of magnitude lower than that of the polycrystalline sample, indicating the grain-boundary scattering is a dominant source of enhanced resistivity in the previous data for polycrystalline samples. The present residual resistivity value for the epitaxial film is comparable to that of SrMoO 3 films as previously reported [9]. A tiny upturn of resistivity was observed below 9 K; at 2 K a negative magnetoresistance is discerned such as 1.2% at 9 T. This behavior might be related to a weak localization effect arising from an impurity scattering.…”
Section: Methodssupporting
confidence: 89%
“…In order to stabilize the Sr 2 MoO 4 phase, the gas condition and substrate temperature during the growth were optimized. As previously reported for the growth of CaMoO 3 and SrMoO 3 films, an argon gas environment is quite effective to realize the highly reductive condition and to avoid the formation of other phases with higher valence states of Mo [9]. In the case of Sr 2 MoO 4 , we found that such an argon gas flow is also necessary to stabilize the Sr 2 MoO 4 phase.…”
Section: Methodssupporting
confidence: 77%
“…The details of the fabrication were described in Ref. 19 . HX photoemission measurements were carried out at BL-47XU of SPring-8.…”
Section: Methodsmentioning
confidence: 99%
“…Nagai et al 18 reported that SrMoO 3 single crystals grown in ultra-low oxygen pressure show resistivity as low as 5.1 µΩcm at 300 K. Recently, Radetinac et al 19 reported the fabrication of high-quality SrMoO 3 thin films using argon gas in the pulsed laser deposition (PLD) process. In this study, we fabricated the same type of thin film which has atomic-level flatness at the surface (with a root-mean-square roughness of 0.2 nm 19 ) and performed hard x-ray (HX) photoemission spectroscopy measurements. By applying bulk-sensitive HX photoemission spectroscopy to the atomically flat surface, we succeeded in obtaining the spectrum of bulk Mo 4d bands.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdates have broad requests in diverse subjects, such as scintillation detector, solid state optical maser,optical fiber, magnetic material, catalyst, light emitting diode, raman laser and so on [1][2][3][4][5][6][7][8]. Among them, strontium molybdate has an enormous deal of benefits due to its distinctive luminescence and structural properties.…”
Section: Introductionmentioning
confidence: 99%